2019
DOI: 10.1002/cbic.201900502
|View full text |Cite
|
Sign up to set email alerts
|

Effective Release of Intracellular Enzymes by Permeating the Cell Membrane with Hydrophobic Deep Eutectic Solvents

Abstract: An efficient and green method is crucial for the recovery of intracellular biological products. The major drawbacks of the conventional cell disruption method are nonselectivity and enzyme denaturation. The permeability of hydrophobic deep eutectic solvents (DESs) to the cell membrane was studied, for the first time, and then hydrophobic DESs were innovatively applied to release intracellular enzymes from recombinant Escherichia coli. After optimization, a DES suspension of l‐menthol/oleic acid (0.5 %, v/v) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The cells were transparent and empty after the component penetration and diffusion in the medium, indicating that DES increased the cell membrane permeability and motivated the efflux of cytoplasmic substances. Cao’s study also showed that the cell membrane was partially damaged by a hydrophobic DES, which was similar to the present results . The E.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The cells were transparent and empty after the component penetration and diffusion in the medium, indicating that DES increased the cell membrane permeability and motivated the efflux of cytoplasmic substances. Cao’s study also showed that the cell membrane was partially damaged by a hydrophobic DES, which was similar to the present results . The E.…”
Section: Resultssupporting
confidence: 91%
“…Cao's study also showed that the cell membrane was partially damaged by a hydrophobic DES, which was similar to the present results. 44 The E. coli cell wall consists of two membranes: the outer layer is comprised of lipopolysaccharides, and the inner layer is a phospholipid bilayer. 45 An investigation of the interaction between a DES and a cell indicated that the HBD inserted in the phospholipid bilayer and that the insertion was dependent on the hydrophobicity of HBDs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…5 TEM images of Escherichia coli cells before any treatment A and after treatment with a suspension of L-menthol/oleic acid, 1:1. With the permission of Cao et al ( 2020 ) …”
Section: Techniques Used To Evaluate Antimicrobial Activity Of Nadessmentioning
confidence: 99%
“…Poorly water-soluble compounds can be extracted from plant biomass in high concentrations and afterwards separated from the (Na)DES by addition of water and subsequent compound precipitation. Thus, (Na)DES, alone or in combination with other methods, can be used to extract various compounds like polyphenols, 47–51 pigments, 52 enzymes 53 and carbohydtrates. 50 Their high solubilizing capacity can be exploited to overcome limited substrate solubility in enzymatic reactions 54 as well as for separation techniques.…”
Section: Localization and Compound Solubility – Why Nades Are Believe...mentioning
confidence: 99%